Strategi Pengembangan Hutan Wakaf Bogor Menggunakan Pendekatan ISM - Rahma Aini Nur; Mohammad Iqbal Irfany; Aini, Rahma (AL-MUZARA'AH, 2024)
Forests will become extinct if they are not managed wisely and sustainably. One of the forestry problems that occur in Indonesia is deforestation or logging activities in forest areas. Waqf Forest is a waqf-based forest conservation innovation that can be a supporting instrument for forest conservation. The problem that is the main focus in the development of waqf forests is how to overcome disaster mitigation in the waqf forest area in terms of reforesting deforested areas, areas prone to landslides and providing access to economic empowerment to the community and problems related to the number of permanent employees in the Bogor Waqf Forest This study aims to describe the Bogor Waqf Forest program, identify key sub-elements of the waqf forest development strategy and analyze the Bogor Waqf Forest development strategy using the Interpretive Structural Model (ISM) approach. The results of the analysis show that the elements of needs and objectives have almost the same key sub-elements, which are related to the legal protection for waqf forests and the main obstacle is the problem of nazhir's professionalism which is the responsibility of the principal actors or institutions mentioned. The achievement of the elements of needs, constraints, and objectives can be fulfilled by the actors or institutions involved through the activities of the key sub-elements, namely the coordination of BWI, WaCIDS, the Ministry of Religion, BAZNAS, Bogor Waqf Forest Foundation, and Regional Governments and related institutions to encourage waqf forest projects.